Answer: First Subtract 5x from both sides. Then subtract 1 from both sides.
Step-by-step explanation: To solve an equation, get all the variables (x, in this example) on one side and all the constants (numbers alone) on the other side of the equation.
The thing to remember about solving an equation is to keep it balanced. Do the same thing on both sides.
When possible, subtract smaller numbers from higher numbers.
5x + 3 = 6x + 1
5x -5x + 3= 6x - 5x + 1
5x-5x =0 on the left side so they "cancel" On the right, 6x-5x = x
3 = x + 1
3 -1 = x +1 -1
On the right 1-1 = 0 So the 1's "cancel" On the left 3-1 = 2
2 = x Rewrite as x = 2 to tell the solution